Identification of Toxic and Hazardous Waste in Motorbike Workshop (Case Study: Pranti Village, Menganti Sub-District, Gresik District) - Pratama Sandi Alala (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2021)
Waste management is great importance conducted to avoid environmental pollutant. Some wastes. There are some wastes of Hazardous and Toxic Materials categories. Motorcycle workshop which is located in Menganti, Gresik Regency, East Java is able to repair three to six motorcycles every day. The workshop area is 6 x3 m2. This workshop produced solid waste. The solid wastes were metal and non-metal. Metal consists of nuts, couplers and welding scraps. Nonmetal wastes were rags, oil, and used tires. Non-metal solid waste was rags which have been contaminated by oil/ rubber solvent, sponges/foam, leather, and imitate leather and plastics used. The emergence of B3 toxic waste (organic) total was 18.200ml for 7 days and the emergence of flammable waste was 4000ml for 7 days. Whereas, the solid waste generated in 7 days was 34.200 grams. In the management of hazardous waste and toxic has general provisions which is used like it must be strong, durable, and it was not easily rusting. Waste has different characteristic if it was kept in a storage. It had potential for mixing from 2 different characteristics of B3 waste and it could give unwanted reaction. B3 waste transportation used a pick up. The vehicle used was not accordance to the standard to transport B3 waste safely and it gave high risk of shocks and it could make the drums overthrown from the pickup.